A novel Cr3+-activated far-red titanate phosphor: synthesis, luminescence enhancement and application prospect. (June 2022) - Zhang, S.; Liu, Y.; Yin, J.; Zhang, X.; Li, Y.; Su, L.; Zhou, Z.; Xia, M.
Abstract: Plant factory, a new agricultural planting technology, has emerged and rapidly grown in recent years, with phosphor conversion light emitting diodes (pc-LEDs) considered as the first choice of source light for the plant factory. In this study, a new type of Cr 3+ -activated Li2 MgTi3 O8 phosphor (LMT: Cr 3+ ) was synthesized by high temperature solid state method. X-Ray diffraction patterns showed that there was no detectable impurity in these samples. The photoluminescence spectra revealed that this phosphor can emit far-red light with the peak at 740 nm excited by ultraviolet and blue light, overlapped well with the PFR . After introducing Zn 2+ ions (LMT: Cr 3+, Zn 2+ ), the luminescence intensity increases by 46% mainly due to the increase of lattice distortion, and internal quantum yield was improved from 25.4% to 41.3% under 365 nm excitation. Finally, the pc-LED devices, consisting of 470 nm chip coated with the optimal phosphor, exhibited good luminescence and overlapping with PFR . These results indicate that the LMT: Cr 3+, Zn 2+ phosphor has the potential application in modern agriculture. Graphical abstract: Image 1 Highlights: A novel Cr 3+ -activated far-red titanate phosphor was synthesized. The emission intensity increased by 46% via Zn 2+ doping. The internal quantum yield increased from 25.4% to 41.3% after modification. The emission is close to the absorption range of PFR and the overlap ratio is 56%.